Immunological properties of embryonic and adult stem cells - Bifari, Francesco (Baishideng Publishing Group Co., Limited, 2010)
The possibility of treating degenerative diseases by stem cell-based approaches is a promising therapeutical option. Among major concerns for the clinical application of stem cells, some derive from the possibility that stem cells may be rejected by the immune system as a consequence of histoincompatibility and that stem cells themselves may interfere with the normal functions of host immune response. Therefore, the immunogenicity and the immunomodulatory properties of stem cells must be carefully addressed. Although these properties are common features of different stem cell types, some peculiarities can be recognized and characterized for their proper clinical use.